2002
DOI: 10.1080/10473289.2002.10470832
|View full text |Cite
|
Sign up to set email alerts
|

Full-Scale Evaluation of Mercury Control with Sorbent Injection and COHPAC at Alabama Power E.C. Gaston

Abstract: The overall objective of this project was to determine the cost and impacts of Hg control using sorbent injection into a Compact Hybrid Particulate Collector (COHPAC) at Alabama Power's Gaston Unit 3. This test is part of a program funded by the U.S. Department of Energy's National Energy Technology Laboratory (NETL) to obtain the necessary information to assess the costs of controlling Hg from coal-fired utility plants that do not have scrubbers for SO 2 control. The economics will be developed based on vario… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0
2

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 3 publications
1
9
0
2
Order By: Relevance
“…17 These data also are shown in Figure 10. Results from the PoCT tests presented in Figure 10 indicate 60-75% Hg removal for this injection concentration.…”
supporting
confidence: 62%
“…17 These data also are shown in Figure 10. Results from the PoCT tests presented in Figure 10 indicate 60-75% Hg removal for this injection concentration.…”
supporting
confidence: 62%
“…A number of pilot-scale experimental data under a fabric filter (baghouse) PMCD configuration have been collected to date, ,,− ,,− most of them using slipstreams from full-scale power plants, to have flue gas conditions representative of real operation. In addition, one experimental campaign of mercury capture with activated carbon in an FF-equipped full-scale power plant (unit 3 at Gaston Power Plant, Alabama, representing nominally 135 MW) has been recently reported . As highlighted before, comparison between model results and pilot- and full-scale experimental data must be considered with care, because under real operating conditions several factors (the presence of gaseous and solid pollutants, temperature gradients, sorbent/flue gas mixing limitations, and sorbent deposition), not taken into account in the model, may influence the mercury removal efficiency.…”
Section: Resultsmentioning
confidence: 99%
“…As a consequence, a larger carbon utilization leading to reduced operating costs is anticipated for FF-equipped facilities. It has been suggested that ESP-equipped power plants could be retrofitted with an additional high air-to-cloth ratio fabric filter to increase the overall mercury removal efficiency of the PMCD and to separate effectively the ESP-collected fly ash from the FF-collected sorbent. ,,, …”
Section: Introductionmentioning
confidence: 99%
“…The U.S. Department of Energy's National Energy Technology Laboratory completed the first full-scale evaluation of mercury control with sorbent injection technology. They mentioned that powderactivated carbon was delivered to the plant in 900-lb supersacks [12]. Obviously, the adsorbent for mercury capture is produced in the laboratory or adsorbent-processing factory.…”
Section: Introductionmentioning
confidence: 99%